Association of body roundness index with circadian syndrome: a cross-sectional study using NHANES data from 2009 to 2018 - Jin-Yan Lan; Yu-hong Song; Yu Ke; Chen-wei An; Chao-He Chen; Li-Xu Tang (Journal of Health, Population and Nutrition)
Abstract Background Obesity is a significant manifestation of Circadian Syndrome (CircS), and the Body Roundness Index (BRI) is one of the anthropometric indicators associated with obesity. However, it remains unclear whether BRI is linked to the risk of CircS. Methods In this population-based cross-sectional study, data from adults aged ≥ 20 years from the 2009–2018 National Health and Nutrition Examination Survey (NHANES) database were analyzed. Logistic regression analysis was employed to investigate the relationship between BRI and CircS after adjusting for various covariates. To further explore the trend of association between different BRI levels and CircS, BRI was categorized into four classes to enhance the robustness of the results. Restricted cubic spline (RCS) analysis was utilized to illustrate the dose-response relationship between BRI and CircS. Additionally, subgroup analyses were performed to assess the consistency and stability of the study results. Results This study included 8,024 participants aged 20 years and older, of whom 2,634 had CircS. In fully adjusted models, BRI was positively associated with the prevalence of CircS (OR = 2.821, 95% CI: 2.038–3.768). When BRI was transformed from a continuous to a categorical variable, higher levels of BRI were correlated with a higher prevalence of CircS compared to the lowest quartile of BRI. RCS analyses demonstrated a positive association between BRI and CircS prevalence, with threshold effect analyses identifying a threshold value of BRI at 5.91. To the left of this threshold, each one-unit increase in BRI elevated the prevalence of CircS by a factor of 2.681 (OR = 2.681, 95% CI: 2.524–2.851). Stratified factorial subgroup analyses indicated that the positive association between BRI and CircS persisted. Conclusion The findings of our cross-sectional study indicate a significant positive correlation between elevated BRI and increased prevalence of CircS.